Innervation of human superficial fascia - Fede, Caterina; Petrelli, Lucia; Pirri, Carmelo; Neuhuber, Winfried; Tiengo, Cesare; Biz, Carlo; De Caro, Raffaele; Schleip, Robert; Stecco, Carla (Frontiers in Neuroanatomy, 2022)
The superficial fascia has only recently been recognized as a specific anatomical structure. Furthermore, whereas it is actually recognized that the innervation of the deep/muscular fascia plays a key role in proprioception and nociception, there are very few studies that have analyzed these characteristics in the superficial fascia. In this work, our group analyzed two different anatomical districts (abdomen and thigh), from volunteer patients, undergoing surgery procedures. Each sample was processed for histological analysis by Hematoxylin&Eosin, and by immuhistochemistry stainings (in 5-micron-paraffin embedded section and in cryosectioned free floating samples), with antibodies specific for nerve fibers: S100 antibody for myelinating and non-myelinating Schwann cells, PGP9.5 antibody as pan-neuronal marker, tyrosine hydroxylase for autonomic innervation. The results revealed a huge innervation: the nervous structures were found above all around blood vessels and close to adipocytes, but they penetrated also in the connective tissue itself and are found in the midst of fibro-adipose tissue. The tissue is pervaded by both thin (mean diameter of 4.8 ± 2.6 µm) and large nerve fiber bundles of greater diameter (21.1 ± 12.2 µm). The ratio S100/TH positivity was equal to 2.96, with a relative percentage of autonomic innervation with of 33.82%. In the light of these findings is evident that the superficial fasciae have a clear and distinct anatomical identity and a specific innervation, which should be considered to better understand their role in thermoregulation, exteroception and pain perception. The knowledge of the superficial fascia may improve grading and developing of different manual approach for treatments of fascial dysfunctions, and the understanding of how some factors like temperature or manual therapies can have an impact on sensitivity of the fascia.